An educational framework for supporting the implementation of the Intelligent Cargo concept. Issue 2 (3rd May 2016) - Baalsrud Hauge, Jannicke
Abstract : The introduction of Intelligent Cargo (IC) solutions in supply chains will support the development and use of advanced information services for freight transportation in Europe. The IC concept allows services to be instantly combined in relation to the capabilities of self-awareness, context-awareness and connection through a global telecommunications network to support a wide range of information services. This leads to a paradigm change, and will have a large impact on organizational structures within the supply chain. Such changes require that the employees are informed and involved in the transformation process, as well as that they are qualified to meet the new requirements. IC leads to paradigm changes, and thus all stakeholders will need additional training in being aware and understanding the solutions and their impact on the supply chain. In order to prepare organizations, a previous research project, EURIDICE has provided a learning framework aimed at providing all necessary training material for a successful introduction of the IC concept. Since the qualification needs are different for each employee, the learning framework is designed to be easily personalized. However, it also offers predefined curricula for specific target groups. The learning framework is implemented as an online tool, using a learning management systems (LMS) system. The aim of the paper is to explain the concept and show how it can be used for other Internet of Things and cyberphysical system solutions as well.